Hieracium mrazii (Asteraceae), a new hybridogenous species from Romania - Szeląg, Zbigniew (Phytotaxa, 2016)
Hieracium mrazii, a new, apomictic, tetraploid (x = 9) species of presumably hybrid origin between sexual diploids, H. transylvanicum and H. umbellatum, is described from the Retezat Mountains, Southern Carpathians, Romania, and illustrated by a photo of the holotype.